A novel rat model of liver regeneration: possible role of cytokine induced neutrophil chemoattractant-1 in augmented liver regeneration. (December 2015) - Dhar, Dipok; Mohammad, Goran; Vyas, Soumil; Broering, Dieter; Malago, Massimo
Abstract Background Liver resection is the mainstay of treatment for most of the liver tumors. Liver has a unique capability to restore the lost volume following resection, however, most of the primary tumors grow in a liver with preexisting parenchymal diseases and secondary tumors often present in multiple liver lobes precluding a safe curative resection. Two-stage hepatectomy and portal vein ligation (PVL) are used to achieve a safer future remnant liver volume (FRLV), however, these procedures take several weeks to achieve adequate FRLV. A recently introduced faster alternative two-stage hepatectomy, also know as associated liver partitioning and portal vein ligation for staged hepatectomy (ALPPS), produces a desirable FRLV in days. Methods To have an insight into the mechanism of ALPPS associated liver regeneration, we reproduced a rat model of ALPPS and compared the results with the PVL group. Results Our results convincingly showed an advantage of the ALPPS procedure over PVL group in terms of early regeneration, however, in 1-week time the amount of regeneration was comparable. An early regeneration in the ALPPS group coincided with an early entry of hepatocytes into the cell proliferation phase, a significant increase in portal pressure and increase in hepatic enzymes in the ALPPS group compared with the PVL group. According to the protein array evaluation of 29 cytokines/chemokines, cytokine induced neutrophil chemoattractant-1 had the highest expression whereas IL-6 had the highest fold (>6 vs PVL group) expression at the early phase of regeneration in the ALPPS group. Conclusions This unique rat model of ALPPS would help to improve our understanding about the liver generation process and also will help in further refinement of the ALPPS procedure for the clinical benefit.